Core–shell upconversion nanoparticles with suitable surface modification to overcome endothelial barrier - Chao Lu; Jianying Ouyang; Jin Zhang (Discover Nano)
Abstract Upconversion nanoparticles (UCNPs), capable of converting near-infrared (NIR) light into high-energy emission, hold significant promise for bioimaging applications. However, the presence of tissue barriers poses a challenge to the effective delivery of nanoparticles (NPs) to target organs. In this study, we demonstrate the core–shell UCNPs modified with cationic biopolymer, i.e., N, N-trimethyl chitosan (TMC), can overcome endothelial barriers. The core–shell UCNP is composed of NaGdF4: Yb3+,Tm3+ (16.7 ± 2.7 nm) as core materials and silica (SiO2) shell. The average particle size of UCNPs@SiO2 is estimated at 26.1 ± 3.7 nm. X-ray diffraction (XRD), transmission electron microscopy (TEM) and element mapping shows the formation of hexagonal crystal structure of β-NaGdF4 and elements doping. The surface of UCNPs@SiO2 has been modified with poly(ethylene glycol) (PEG) to enhance water dispersibility and colloidal stability, and further modified with TMC with the zeta potential increasing from -2.1 ± 0.96 mV to 26.9 ± 12.6 mV. No significant toxic effect is imposed to HUVECs when the cells are treated with core–shell UCNPs with surface modification up to 250 µg/mL. The transport ability of the core–shell UCNPs has been evaluated by using the in vitro endothelial barrier model. Transepithelial electrical resistance (TEER) and immunofluorescence staining of tight junction proteins have been employed to verify the integrity of the in vitro endothelial barrier model. The results indicate that the transport percentage of the UCNPs@SiO2 with PEG and TMC through the model is up to 4.56%, which is twice higher than that of the UCNPs@SiO2 with PEG but without TMC and six times that of the UCNPs@SiO2.